Clinical Impact of COVID-19 on Multi-Drug-Resistant Gram-Negative Bacilli Bloodstream Infections in an Intensive Care Unit Setting: Two Pandemics Compared - Francesco Cogliati Dezza; Gabriele Arcari; Federica Alessi; Serena Valeri; Ambrogio Curtolo; Federica Sacco; Giancarlo Ceccarelli; Giammarco Raponi; Francesco Alessandri; Claudio Maria Mastroianni; Mario Venditti; Alessandra Oliva (MDPI AG, 2022)
Two mutually related pandemics are ongoing worldwide: the COVID-19 and antimicrobial resistance pandemics. This study aims to evaluate the impact of COVID-19 on multi-drug-resistant Gram-negative bacteria (MDR-GN) bloodstream infections (BSIs) in a single intensive care unit (ICU). We conducted a retrospective study including patients admitted to the ICU, reorganized for COVID-19 patients' healthcare, with at least one confirmed MDR-GN BSI during 2019-2020. We compared clinical and microbiological features, incidence density, antibiotic therapy and mortality rate in pre- and during-COVID-19 pandemic periods. We estimated the impact of COVID-19 on mortality by means of univariate Cox regression analyses. A total of 46 patients were included in the study (28 non-COVID-19/18 COVID-19). Overall, 63 BSI episodes occurred (44/19), and non-COVID-19 patients had a higher incidence of MDR-GN BSIs and were more likely to present K. pneumoniae BSIs, while the COVID-19 group showed more A. baumannii BSIs with higher per pathogen incidence. COVID-19 patients presented more critical conditions at the BSI onset, a shorter hospitalization time from BSI to death and higher 30-day mortality rate from BSI onset. COVID-19 and septic shock were associated with 30-day mortality from MDR-GN BSIs, while early active therapy was a protective factor. In conclusion, COVID-19 showed a negative impact on patients with MDR-GN BSIs admitted to the ICU.